The development of bio-based adhesives for the manufacture of structural-use engineered wood products - Harris, Laurelyn (My University, 2025)
The increasing demand for sustainable construction has intensified research into bio-based adhesives for engineered wood products (EWPs), aiming to reduce the environmental and health impacts associated with conventional synthetic-based adhesives. Synthetic adhesives such as phenol-formaldehyde, resorcinol-formaldehyde, and polyurethane provide high strength and durability but emit volatile organic compounds (VOCs) and formaldehyde, contributing to poor indoor air quality and hindering end-of-life recyclability. To support green building initiatives and circular economic goals, this report compiles, evaluates, and compares research on lignin-based and soy protein-based bio-adhesives to determine their suitability for structural and exterior applications in EWPs. This report provides a comprehensive review of existing studies to identify formulation methods, material sources, chemical properties, and performance outcomes of lignin-based and soy protein-based adhesives. Lignin adhesives utilize biorefinery by-products and bio-reactants such as glyoxal to replace petroleum-derived phenol and formaldehyde, while soy protein adhesives, derived from defatted soy flour or soy protein isolate, eliminate formaldehyde and can be modified to improve bond strength and water resistance. The report organizes and synthesizes this information into comparative tables and figures summarizing mechanical performance metrics, such as shear strength, modulus of elasticity, and moisture resistance, under various test conditions. The findings of this report demonstrate that both lignin and soy-protein-based adhesives show strong potential to meet or approach the performance of current synthetic adhesives while offering significant environmental and health benefits. However, limitations remain in water resistance, curing time, and large-scale manufacturing feasibility. The report serves as a consolidated reference for researchers and industry professionals seeking to advance the application of bio-adhesives in structural-use EWPs. By presenting a clear comparison of formulation strategies, performance outcomes, and areas for continued development, this report contributes to the progression of safer, recyclable, and low-emission building materials essential to achieving long-term sustainability in the construction industry.
Keywords: Bio-based adhesives; Engineered wood products; Lignin-based adhesives; Soy protein adhesives; Green building materials; Performance evaluation